Analisis Efektivitas Skul.id untuk Absensi dan Penugasan Mahasiswa Magang: Studi Kasus di PT Telkomsel Branch Surabaya - Nuraini, Nurul; Iryanti, Endang (Policy, Law and Political Research Center, 2025)
Digital transformation in internship management demands a system that is not only administratively efficient but also relevant to the practical needs of students and companies. This research aims to assess the effectiveness of Skul.id as a supporting instrument for student internships at PT Telkomsel Surabaya Branch using a descriptive qualitative approach. Effectiveness is measured through three indicators: program understanding, satisfaction, and goal achievement. The results show that Skul.id is effective in supporting daily attendance and document-based assignment collection, but still faces constraints such as limited assignment formats and unstable notifications. This finding confirms that the effectiveness of digital apprenticeship systems is influenced by the integration of technical quality and alignment with students' work needs. Practically speaking, the development of similar applications needs to consider the integration of more diverse assignment formats and improved notification reliability so that the digital system can serve as a sustainable model for the digitalisation of internships at other institutions.